PLTA Pikohidro untuk Masyarakat Desa Batu Layang Kabupaten Bengkulu Utara - Angky Puspawan; Helmizar; Mohammad Anshori (Program Studi Teknik Mesin, Fakultas Teknik Universitas Bengkulu, 2024)
Rural areas far from the city, people with less than average income have the right to get adequate sources of electrical energy. The availability of electricity is compulsory for economic productivity, supporting education and health. The construction of piko-hydroelectric power plant is one solution for this purpose. The advantages are affordable construction and maintenance costs as well as transferable technology to villagers. The object of devotion in Batulayang Village is technology transfer to the community. This activity received a response and enthusiasm from residents and the local administrator.